Person-centred and Experiential Therapies : Contemporary Approaches and Issues in Practice. - Wilkins, Paul (SAGE Publications, 2015)
An essential new guide for any person-centred trainee or practitioner, this book offers a unique focus on how to practise the various contemporary person-centred therapies.